Rare perinatal infections - А. А. Fadeeva; H. A. Sarkisyan; O. V. Molochkova; N. Yu. Egorova; А. А. Komarova; D. M. Mushcherova; A. P. Khokhlova; O. I. Savateeva; P. V. Shumilov (LLC "Diagnostics and Vaccines", 2024)
Congenital viral infections are one of the pressing issues in modern neonatology. Due to the fact that viremia is a common stage in the infection process, the fetus is at high risk of intrauterine hematogenic infection, which can harm various organs and systems. The most frequently observed manifestations of congential viral infections are: intrauterine growth restriction (IUGR), micro- and macrocephaly, fetal hydrocephalus, hepatosplenomegaly, pneumonia, bone lesions, rash and haematological abnormalities. Even though these clinical manifestations are not specific, identifying the etiological factor is often a necessary step to determine the future management of the newborn. The aim of this paper is to collect and summarize literary data on lymphocytic choriomeningitis virus (LCMV) and Zika virus. Results: congenital infections caused by LCMV and Zika virus share similar clinical features. Laboratory and instrumental diagnostic methods facilitate carrying out the differential diagnosis and establishing prognosis and the best clinical approach to the patient.